Economic Feeding of Pigs in Mizoram: A Field Study for Assessment of Nutritional Constraints and Identifying the Useful Local Feed Resources for Economic Feeding - Buragohain, Rajat; Upadhyaya, Kalidas (International Journal of Bio-resource and Stress Management, 2022)
The study was conducted in the Department of Animal Nutrition, College of Veterinary Sciences and Animal Husbandry, Central Agricultural University (Imphal), Aizawl, Mizoram during 2018-19. The objective of the research was to assess the nutritional constraints of feeding pigs in Mizoram and to put forward some solutions by identifying and utilizing local feed resources for economic feeding. Numbers of unconventional feeds were used for feeding pigs in Mizoram and fourteen among them were identified to be commonly used in day-to-day preparation of home-made cooked feed, which was the composite feed given to all categories of pigs. Constraints of the existing feeding practice were identified as high cost of conventional feeds, low dry matter intake causing deficient energy consumption, poor digestibility of nutrients when home-made cooked feed was fed, high tannin content of unconventional feeds. Except crude protein, apparent digestibility of dry matter, ether extract, crude fibre, nitrogen free extract and organic matter were low under the existing feeding practice. Based on nutrient contents, unconventional local feeds were categorized as protein and energy rich for substitution of conventional ingredients in ration formulation. Few rations with unconventional feeds substituting conventional ones suggested for grower and finisher pigs. Complete feed block of conventional and unconventional feeds was found acceptable to pigs. The study indicated the possibility of economic feeding of pigs by utilizing the local feeds keeping in view their nutritive and anti-nutritive contents and taking into consideration the constraints associated with nutrient intakes under the existing feeding management.